Effect of curing regimes towards carbonation resistance of green lightweight aggregate concrete containing POFA as partial cement replacement - Nur Azzimah, Zamri; Khairunisa, Muthusamy; Mohd Hanafi, Hashim; Hamizah, Mokhtar; Muhammad Nazrin Akmal, Ahmad Zawawi (Springer, 2024)
In construction, carbonation is one of the major causes of reinforced concrete deterioration at site. Concrete carbonation causes embedded steel reinforcements to corrode, which resulted in concrete expansion and cracking. Concurrently, awareness towards reducing waste disposed by palm oil industry namely palm oil fuel ash (POFA) that have an impact towards environment has initiated researchers to convert these waste materials towards more environmentally friendly building materials. Meanwhile, palm oil clinker (POC), another waste generated from palm oil industry is abundantly produced which causes soil erosion. The present investigation looks into the effect of POFA content as partial cement replacement towards carbonation resistance of palm oil clinker lightweight aggregate concrete (POC LWAC). Performance of control palm oil clinker lightweight aggregate concrete and palm oil clinker lightweight aggregate concrete containing POFA as partial cement replacement under different curing regimes have been investigated in this research by using prisms of 100 mm × 100 mm × 500 mm that were water and air cured before subjected to carbonation test. The test results indicate that suitable integration of POFA content would results in pozzolanic reaction and filling effect which are beneficial in minimizing the pore size and volumes, thus reducing the carbonation rate and promotes better durability towards carbonation. Integration of 10% POFA considerably enhanced the carbonation resistance of POC lightweight aggregate concrete compared to other mixes. The test also shows that between the two different curing regimes, water curing resulted in better results in terms of carbonation resistance as it evident from the low porosity result conducted.